Intimate Citizenship : Private Decisions and Public Dialogues - Plummer, Kenneth (Book collections on Project MUSE., 2003)
"In this study, sociologist Ken Plummer examines the transformations taking place in the realm of intimacy and the conflicts - the "intimate troubles"--To which these changes constantly give rise. In surveying the intimate possibilities now available to us and the issues swirling around them, Plummer focuses especially on the overlap of public and private. Increasingly, our most private decisions are bound up with public institutions such as legal codes, the medical system, or the media."--Jacket.